2017
DOI: 10.1038/srep39673
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a missing source of efficient ice nuclei

Abstract: It has been known for several decades that some bioaerosols, such as ice-nucleation-active (INA) bacteria, especially Pseudomonas syringae strains, may play a critical potential role in the formation of clouds and precipitation. We investigated bacterial and fungal ice nuclei (IN) in rainwater samples collected from the Hulunber temperate grasslands in North China. The median freezing temperatures (T50) for three years’ worth of unprocessed rain samples were greater than −10 °C based on immersion freezing test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Only a few genera were unique to one sample type, the discrimination by NMDS was due to changes in relative abundance between sample types, which indicated an accumulation of most INP-containing bacteria in the wet phases, and only single species associated with air. Erwinia and Xanthomonas were unique in air in this dataset, though they are usually abundant in the environment, but also absent in other water-based IN-surveys (Du et al 2017). Zweifel et al (2012) found Erwinia and Pantoea in low frequencies, but recurringly in free tropospheric air samples.…”
Section: Inp-containing Bacteria Are Selected For Precipitationmentioning
confidence: 79%
“…Only a few genera were unique to one sample type, the discrimination by NMDS was due to changes in relative abundance between sample types, which indicated an accumulation of most INP-containing bacteria in the wet phases, and only single species associated with air. Erwinia and Xanthomonas were unique in air in this dataset, though they are usually abundant in the environment, but also absent in other water-based IN-surveys (Du et al 2017). Zweifel et al (2012) found Erwinia and Pantoea in low frequencies, but recurringly in free tropospheric air samples.…”
Section: Inp-containing Bacteria Are Selected For Precipitationmentioning
confidence: 79%
“…This differs from the Gammaproteobacteria, for which INA is dependent on cell integrity and for which the number of IN is limited to the number of bacterial cells in the atmosphere. Moreover, because of their size, bacterial LINA-like molecules could represent some of the abundant nanometer-sized Ice + particles active at warm temperatures identified by Vali (1966) andO'Sullivan et al (2015) and more recently by Du et al (2017) or Šantl-Temkiv et al (2015.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria are generally larger than 0.3 μm in equivalent size (Lighthart & Mohr, 1994). Individual airborne bacteria are typically on the order of~1 μm or less in size (Després et al, 2012;Pósfai et al, 2003), although smaller microscale and nanoscale bacterial fragments might be present in the atmosphere (Du et al, 2017;Šantl-Temkiv et al, 2015). In addition, bacteria suspended in PBS were filtered on 0.2 μm pore black polycarbonate filters for enumeration.…”
Section: Bacterial Concentration and Viabilitymentioning
confidence: 99%